X-Ray Emissions from Accreting White Dwarfs: A Review. (19th April 2017) - Mukai, K.
Abstract: Interacting binaries in which a white dwarf accretes material from a companion—cataclysmic variables (CVs) in which the mass donor is a Roche-lobe filling star on or near the main sequence, and symbiotic stars in which the mass donor is a late type giant—are relatively commonplace. They display a wide range of behaviors in the optical, X-rays, and other wavelengths, which still often baffle observers and theorists alike. Here I review the existing body of research on X-ray emissions from these objects for the benefits of both experts and newcomers to the field. I provide introductions to the past and current X-ray observatories, the types of known X-ray emissions from these objects, and the data analysis techniques relevant to this field. I then summarize of our knowledge regarding the X-ray emissions from magnetic CVs, non-magnetic CVs and symbiotic stars, and novae in eruption. I also discuss space density and the X-ray luminosity functions of these binaries and their contribution to the integrated X-ray emission from the Galaxy. I then discuss open questions and future prospects.